2014
DOI: 10.1088/0960-1317/24/3/035017
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of bulk Sylgard 184 for microfluidics and microengineering

Abstract: Polydimethylsiloxane (PDMS) elastomers are extensively used for soft lithographic replication of microstructures in microfluidic and micro-engineering applications. Elastomeric microstructures are commonly required to fulfil an explicit mechanical role and accordingly their mechanical properties can critically affect device performance. The mechanical properties of elastomers are known to vary with both curing and operational temperatures. However, even for the elastomer most commonly employed in microfluidic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

64
892
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,266 publications
(960 citation statements)
references
References 23 publications
64
892
3
1
Order By: Relevance
“…In this paper, we systematically studied the effects of silica nanoparticles on the properties of the most commonly used PDMS in microfluidics, Sylgard 184 (Dow Corning Corporation, Midland, MI, USA) [3,5,10,11,20]. The thermal and mechanical stabilities, swelling characteristics and transparency were all examined.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we systematically studied the effects of silica nanoparticles on the properties of the most commonly used PDMS in microfluidics, Sylgard 184 (Dow Corning Corporation, Midland, MI, USA) [3,5,10,11,20]. The thermal and mechanical stabilities, swelling characteristics and transparency were all examined.…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, PDMS has a tensile Young's modulus in the range of 1.32-2.97 MPa, slightly higher than that of skin [33][34][35]. It is proved that compatible component can endow the polymer blend improved mechanical properties [36].…”
Section: Resultsmentioning
confidence: 96%
“…have shown that YPDMS can be in the range of the megapascal (Johnston et al, 2014). As a rule, it has been demonstrated that YPDMS strongly varies on both the curing agent/base elastomer ratio, temperature, baking time, and baking conditions (Fuard et al, 2008;Johnston et al, 2014).…”
Section: Young's Modulus Of M-srementioning
confidence: 92%
“…have shown that YPDMS can be in the range of the megapascal (Johnston et al, 2014). As a rule, it has been demonstrated that YPDMS strongly varies on both the curing agent/base elastomer ratio, temperature, baking time, and baking conditions (Fuard et al, 2008;Johnston et al, 2014). Specifically, in Brau et al (2011) and Terwagne et al (2014), the Young's modulus of PDMS is shown to vary between 10 and 1,000 kPa depending of the aforementioned technological conditions.…”
Section: Young's Modulus Of M-srementioning
confidence: 94%